The Influence Of Fintech Payment, Financial Literacy, And Lifestyle On Financial Management Of Shopee Paylater Users In Pontianak City With Income As A Moderating Variable - Aqcahya, Nabila; Safitri, Heni; Hariyanto, Dedi (UNIVERSITAS PAKUAN, 2024)
In an increasingly advanced digital era, technological innovations continue to develop, especially in payment systems. The use of financial technology (fintech) is growing, especially in urban areas such as Pontianak City. One of the most prominent innovations from fintech is the PayLater feature. From the phenomena that arise related to the widespread use of the PayLater feature, the purpose of this study is to examine the effect of Fintech Payment, Financial Literacy, and Lifestyle on the financial management of Shopee Paylater users in Pontianak City, with income as a moderating variable. This research uses associative methods and quantitative approaches. The data were analyzed using Moderated Regression Analysis (MRA) with SPSS software after being collected from 150 respondents through a questionnaire. The calculation results for Equation 1 are as follows: Y = 26,886 + (1,049 x 5) + (1,362 x 4) + (3,076 x 3) = 46,807. These results indicate that the financial management score derived from the direct influence of Fintech Payment, Financial Literacy, and Lifestyle is 46.807. The calculation results for Equation 2 are as follows: Y = 26.886 + (1.049 x 5) + (1.362 x 4) + (3.076 x 3) + (2.027 x 6) + (0.039 x 5 x 6) + (0.061 x 4 x 6) + (0.114 x 3 x 6) = 63.655. This result shows that the financial management score, after considering the effect of income (Z) and its interaction with Fintech Payment, Financial Literacy, and Lifestyle, is 63.655. These results indicate that the financial management score, after considering the effect of income (Z) and its interaction with Fintech Payment, Financial Literacy, and Lifestyle, is 63,655. The results of this study indicate that Fintech Payment, Financial Literacy, and Lifestyle show positive and significant results on Financial Management directly. The results of the influence of Fintech Payment, Financial Literacy, and Lifestyle which are moderated as moderating variable also get the result that income can moderate positively and significantly on financial management.